Pengaruh Kompensasi Finansial Dan Kompensasi Nonfinansial Terhadap Kinerja Pegawai SAMSAT Pesisir Barat Lampung - Ana Septiani; Kuncoro Budi Riyanto; Eko Aprinato (Jurnal Manajemen DIVERSIFIKASI, 2024)
This study aims to determine whether non-financial compensation and financialcompensation have a partial or simultaneous influence on the performance of employees atthe West Coast Samsat Office. The research method uses a quantitative approach throughobservation and distribution of questionnaires and is processed with the SPSS version 25program. The sampling technique uses saturated sampling with sample calculations obtainedby 32 representative employees in filling out the questionnaire. The analysis tool usesmultiple regression with partial (t) and simultaneous (f) test decisions. The results of thestudy prove that non-financial compensation has an effect on employee performance, whilefinancial compensation has no effect on employee performance. Simultaneously both have aninfluence in improving employee performance.